PWE-147 Systematic study of gastrointestinal symptoms and quality of life in cystic fibrosis: the 'CF gut'. (8th June 2018) - Hayee, Bu'Hussain; Watson, Kerry-Lee; Howard, Emma; Hutchings, Penelope; Campbell, Sanchika; Simpson, Anna; Elston, Caroline
Abstract : Introduction: The 'CF gut' is a novel term encompassing the range of gastrointestinal (GI) symptoms recognised in patients with cystic fibrosis (CF). There are no accepted or validated assessment tools and neither the range nor the frequency of symptoms has been described. Evidence from our CF-GI clinic demonstrated that symptoms were not accounted for by pancreatic insufficiency (PI) and appeared to correspond to those seen in IBS. These symptoms will impact quality of life (QOL) outside of pulmonary morbidity, therefore it is not clear whether current CF-related QOL tools are sufficient. Methods: Consecutive patients attending specialist CF clinics were asked to complete questionnaires: Patient Health (PHQ-9); Generalised Anxiety (GAD-7); GI symptom rating scale (GSRS); IBS symptom severity score (IBS-SSS); CF-related quality of life (CFQR). Demographics, BMI, CF genotype, PI status and enzyme replacement therapy (PERT) were recorded. Patients with pre-existing coeliac disease or inflammatory bowel disease were excluded. Questionnaires were altered to remove the term 'IBS' and patients were asked about 'GI symptoms' instead. Results: Results from the total cohort of 176 patients will be forthcoming, but we present interim data from 107 (mean age 27.8±9.6 y; 60 F; 94 PI (88%) of whom 2 were not taking PERT; mean BMI 22.1 kg/m 2, FEV1 59% predicted). 53 (49.5%) were ΔF508 homozygous. 69/107 (65%) met Rome IV criteria for IBS, with 47 (44%) reporting significant symptoms (IBS-SSS >80). Using the GSRS we created a 'heatmap' to describe the range and severity of symptoms as IBS-SSS increased (figure: 'traffic light' colour chart for mild-moderate-severe, columns 1–11 are each descriptor in the GSRS; rows are individual patients with IBS-SSS increasing down left-most column). With patients grouped as IBS-SSS <80 or>80, significant differences were observed in anxiety and depression as well as across all domains of the CFQR. There was no correlation between IBS-SSS and any CFQR domain (particularly that relating to GI symptoms), suggesting that the latter is insufficient to describe the CF gut. Conclusion: This is the first ever systematic study using validated symptom scores to describe the range of GI symptoms in CF. These do not correlate with PERT or genotype and appear to be captured well by the IBS-SSS, but not the CFQR. Further work will be aimed at establishing accurate screening and assessment tools for this phenotype. Therapeutic trials in CF may use these already validated tools to demonstrate a positive impact on 'non-respiratory' symptoms and QOL.